PERFORMANCE OF VACUUM CONSOLIDATION IN A THICK CLAYEY DEPOSIT IN SHANGHAI - Y. J. Wu; Y. C. Yuan; J. C. Chai (Lowland Technology International, 2013)
A vacuum consolidation test was successfully carried out in a (more than 25 m) thick soft clayey deposit in Shanghai. At the site, there is a clayey silt layer located about 5.3 to 6.8 m depth with a relative higher hydraulic conductivity, and a cement deep mixing formed cut-off wall was able to prevent the vacuum leakage through this layer. Prefabricated vertical drains (PVDs) were installed with a spacing of 1.4 m and triangular pattern to a depth of 14 m. The measured results indicate that the degree of vacuum consolidation reached more that 90% in PVD improved zone for a period of about 38 days. Analysis results indicate that the vacuum pressure induced ground deformations can be calculated reasonably well by a previously proposed method. Further field monitoring results whow that one month after stopping the vacuum loading, 10 to 65% of the vacuum pressure induced lateral displacement was rebounded, and the percentage rebounding increased with the depth.